FINANCIAL HARVESTMENT STRATAGEM – A PANOROMA OF SALARIED INVESTORS - N. Sathya, M. Rani Subathra (International Journal of Advanced Science and Technology, 2020)
Financial harvestment Stratagem nothing but an investment activity in various financial schemes, invested in current scenario to be utilized in future or at the time of crisis. In this process, planning plays a vital role in this act. A monthly salaried investor may invest in any of the following like Capital markets, Fixed Deposits in various financial institutions, PPF’s, Postal department, Life Insurance, Real Estate, commodities market and so on. An act of investment controls an individual’s spending style and inculcate the habit of savings. The primary data for this study is collected by using simple random sampling method with the sample size of 40 salaried investors through a structured questionnaire. This paper is discussed about the investment panorama of salaried investors working in various sectors with respect to Chennai city. The present study is a shot to analyse the investment stratagem of salaried investors towards monetary benefits. It reveals that, guesstimate of investment involves accessing the various pin on of investments like return, risk, liquidity, tax benefits and convenience are the key attributes which taken into discussion before involving into any mode of investment.